Performing Modularity: Competing Rules, Performative Struggles and the Effect of Organizational Theories on the Organization. Issue 12 (December 2014) - D'Adderio, Luciana; Pollock, Neil
We address the effect of organizational theories on the organization by focusing on how modularity, a widespread and influential organizational theory, performs a modular organization. While scholars have offered opposing arguments for the influence of this theory—i.e. that it either succeeds or fails to "produce" modular organizations—we show just how and how far modularity is enacted and shapes the organization, and how it may be shaped in turn. Drawing on recent advances in performativity theory we thus contribute to modularity by showing how the modular organization emerges over time as the outcome of performative struggles among competing and complementary theories and how these struggles contribute to modifying the theory and "designing" organizations. We also add to performativity by theorizing the competition between multiple theories, the emergence of unexpected consequences or "errors", and their implications for organizational practices and boundaries.